2018
DOI: 10.1080/09712119.2018.1434528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietaryCentrosema pubescensleaf meal on growth and reproductive traits ofArchachatina marginatasnails

Abstract: This study was conducted to determine the effect on growth and reproductive performance of supplementing dried Centrosema pubescens leaf meal to Archachatina marginata snails. A total of 80 growing, medium-sized A. marginata snails were used. Twenty snails were randomly assigned to one of the four experimental diets as T 1 , T 2 , T 3 , and T 4 containing 0%, 5%, 10%, and 15% dietary inclusion levels of dried C. pubescens leaves, respectively. Each diet constituted a treatment and each treatment was replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This corroborates other reports in rabbits, poultry that leaf meals enhance reproduction and fertility (Ewuola et al 2012). The result of this study is in agreement with Ejidike ( 2007) and Oyeagu et al (2018) that snails fed diets containing concentrate feed and herbs performed better than those that received only concentrate or herbs. The result of this study is in agreement with Ejidike et al (2002) that both growth and reproductive performance of African giant land snails (A. marginata) were better when their diets are supplemented with natural plant food materials than the snails that were placed on pure concentrate diets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This corroborates other reports in rabbits, poultry that leaf meals enhance reproduction and fertility (Ewuola et al 2012). The result of this study is in agreement with Ejidike ( 2007) and Oyeagu et al (2018) that snails fed diets containing concentrate feed and herbs performed better than those that received only concentrate or herbs. The result of this study is in agreement with Ejidike et al (2002) that both growth and reproductive performance of African giant land snails (A. marginata) were better when their diets are supplemented with natural plant food materials than the snails that were placed on pure concentrate diets.…”
Section: Discussionsupporting
confidence: 92%
“…Thompson and Sheldon (2004) also reported that poor nutrition affects snail growth and causes a drop in the reproductive performance, this is evident in the result of laying snails fed roughage/natural plant material (UPWP) which had the least reproductive performance as compared to concentrate GNCD-LLLM fed snails. According to Amaefule and Onwudike (2000), Ani and Okeke (2003), Esonu et al (2003), Oyeagu et al (2015) and Oyeagu et al (2018), the most important factor influencing the performance of animals under captivity is the quality of diet offered to the animals. This study corroborates the claim of Nyameasem and Borketey-La (2014) that layer mash (a concentrate ration) supported reproduction in the snails better than Pawpaw fruit diet which gave the poorest result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nutritional superiority of soybeans may have affected the fertility and hatchability rates with a lesser percentage of mortality of the embryo. Agreeing to Oyeagu et al [9], the most vital factor impelling the performance of animals in captivity, all other factors being constant, is the quality of diet offered to the animals.…”
Section: Reproductive Characteristicsmentioning
confidence: 96%